Investigating the effect of entrepreneurial competencies on business performance among early stage entrepreneurs Global Entrepreneurship Monitor (GEM 2010 survey data) - Mahtab Barazandeh; Kourosh Parvizian; Mehdi Alizadeh; Saber Khosravi (Journal of Global Entrepreneurship Research, 2015)
Entrepreneurs of this era need to be more competent and skillful compared to businessmen working in the beginning of this century. A robust body of knowledge has grown around entrepreneurs' need for superior skills and personality characteristics; the ones that enables them to effectively compete and survive. In this study, we analyzed the relationship between entrepreneurial competencies along with social norms and entrepreneurs' business performance. Data of GEM gathered during 2010 was utilized and 125 cases was selected from 59 member countries. Confirmatory factor analysis showed that social image of entrepreneurs is a better measure than national attitude toward entrepreneurship for the construct "entrepreneurial social norms" based on their factor loadings. For the same reason, entrepreneurial skills remained as the measure of entrepreneurial competencies and entrepreneurial personality measure was dropped. And, for the dependent variable "performance", growth and innovation remained as a more powerful measures than export. Finally, the positive effect of entrepreneurial competencies on business performance was supported by the data and results revealed that there is a positive effect between entrepreneurial social norms on entrepreneurs' competencies which conforms the mediating role of entrepreneurial competencies. However, the data did not support the direct effect of entrepreneurial social norms on performance.
Keywords: 650; Entrepreneurial competency; Business performance; Social norms; GlobalEntrepreneurship Monitor (GEM)